Strengthening and transformation of the Islamic education system in Malaysia - Suhid, Asmawati (Universitas Islam Negeri Syarif Hidayatullah, 2018)
Education is an important aspect in fulfilling the mission and human development agenda. Hence, Islam places great importance in education as was stated in the first verse revealed to the Prophet Muhammad (PBUH). In Malaysia, education is also a priority in the country’s development including Islamic education. The Islamic Education System in Malaysia is constantly evolving and changing in order to meet the needs and demands of the society. Parents and societies who are increasingly interested and realised the importance of Islamic education have created various forms and types of Islamic education. As an example, the emergence of Maahad Tahfiz, Ulul Albab programme, private Islamic Schools, Darul Quran and the J-QAF programme showed a very encouraging improvement. Attention is also given to the children of young prisoners and married teenagers in order they are not left behind in the mainstream education. Hence, this paper will discuss the development, strengthening and transformation of the Islamic education system in Malaysia besides highlighting some research findings that support this discussion.